Sclerosing cholangitis in a patient treated with nivolumab. Issue 5 (28th May 2021) - Talbot, Sam; MacLaren, Vivienne; Lafferty, Heather
Abstract : A 69-year-old retired miner with stage 4 non-small-cell lung cancer presented with a 2-month history of obstructive liver function tests following nivolumab immunotherapy. His case had not responded to high dose prednisolone or mycophenolate and he was admitted for investigation. MR cholangiopancreatography demonstrated areas of intrahepatic biliary tree beading and stricturing, in keeping with sclerosing cholangitis. Prednisolone and mycophenolate were stopped and ursodeoxycholic acid commenced with subsequent partial improvement of the patient's liver function tests.